A discretized model for enzymatic hydrolysis of cellulose in a fed-batch process. (March 2017) - Tervasmäki, Petri; Sotaniemi, Ville; Kangas, Jani; Taskila, Sanna; Ojamo, Heikki; Tanskanen, Juha
Graphical abstract: Highlights: Kinetic model with rate decreasing factors for fed-batch enzymatic hydrolysis. Substrate discretization elucidates the importance of rate decreasing phenomena. Parametric studies reveal the reliability of the model and its parameters. The model handles well a wide range of operation conditions and literature data. Abstract: In the enzymatic hydrolysis of cellulose, several phenomena have been proposed to cause a decrease in the reaction rate with increasing conversion. The importance of each phenomenon is difficult to distinguish from batch hydrolysis data. Thus, kinetic models for the enzymatic hydrolysis of cellulose often suffer from poor parameter identifiability. This work presents a model that is applicable to fed-batch hydrolysis by discretizing the substrate based on the feeding time. Different scenarios are tested to explain the observed decrease in reaction rate with increasing conversion, and comprehensive assessment of the parameter sensitivities is carried out. The proposed model performed well in the broad range of experimental conditions used in this study and when compared to literature data. Furthermore, the use of data from fed-batch experiments and discretization of the model substrate to populations was found to be very informative when assessing the importance of the rate-decreasing phenomena in the model.